Limites do ultramar português, possibilidades para Angola : o debate político em torno do problema colonial (1951-1975) - Peixoto, Carolina Barros Tavares (2009)
Considering colonialism and anti-colonialism in a dialectic regard this work explores the ideas in witch the Portuguese and Angolan political activities to solve the colonial issue between 1951 and 1975 were based. We were doing an analysis of the multiple perspectives about the colonial problems and we hope to show the process that resulted in the independence of Angola.